Inhibition of Cpeb3 ribozyme elevates CPEB3 protein expression and polyadenylation of its target mRNAs and enhances object location memory - Claire C Chen; Joseph Han; Carlene A Chinn; Jacob S Rounds; Xiang Li; Mehran Nikan; Marie Myszka; Liqi Tong; Luiz FM Passalacqua; Timothy Bredy; Marcelo A Wood; Andrej Luptak (eLife, 2024)
A self-cleaving ribozyme that maps to an intron of the cytoplasmic polyadenylation element-binding protein 3 (Cpeb3) gene is thought to play a role in human episodic memory, but the underlying mechanisms mediating this effect are not known. We tested the activity of the murine sequence and found that the ribozyme’s self-scission half-life matches the time it takes an RNA polymerase to reach the immediate downstream exon, suggesting that the ribozyme-dependent intron cleavage is tuned to co-transcriptional splicing of the Cpeb3 mRNA. Our studies also reveal that the murine ribozyme modulates maturation of its harboring mRNA in both cultured cortical neurons and the hippocampus: inhibition of the ribozyme using an antisense oligonucleotide leads to increased CPEB3 protein expression, which enhances polyadenylation and translation of localized plasticity-related target mRNAs, and subsequently strengthens hippocampal-dependent long-term memory. These findings reveal a previously unknown role for self-cleaving ribozyme activity in regulating experience-induced co-transcriptional and local translational processes required for learning and memory.